Seroprevalence of adeno-associated virus types 1, 2, 3, 4, 5, 6, 8, and 9 in a Basque cohort of healthy donors - Navarro-Oliveros, Miguel; Vidaurrazaga, Ander; Soares Guerra, Gabriel; Castellana, Donatello; Embade, Nieves; Millet, Oscar; Marigorta, Urko M; Abrescia, Nicola G A (Scientific reports, 2024)
Adeno-associated viruses (AAVs) are promising gene therapy vectors, but challenges arise when treating patients with preexisting neutralizing antibodies. Worldwide seroprevalence studies provide snapshots of existing immunity in diverse populations. Owing to the uniqueness of the Basque socio-geographical landscape, we investigated the seroprevalence of eight AAV serotypes in residents of the Basque Country. We found the highest seroprevalence of AAV3, and the lowest seroprevalence of AAV9. Additionally, less than 50% of the Basque population has neutralizing antibodies against AAV4, AAV6, and AAV9. Our findings provide insight into AAV infections in the Basque region, public health, and the development of AAV-based therapeutics.
Keywords: Female; lidé středního věku; Španělsko; Spain; Serogroup; kohortové studie; mužské pohlaví; mladý dospělý; neutralizující protilátky; Humans; dospělí; infekce viry z čeledi Parvoviridae; Dependovirus; Antibodies, Viral; lidé; Parvoviridae Infections; Middle Aged; Cohort Studies; séroepidemiologické studie; ženské pohlaví; Young Adult; séroskupina; protilátky virové; Adult; Seroepidemiologic Studies; Antibodies, Neutralizing; Male